Activated alumina-based adsorption and recovery of excess fluoride ions subsequent to calcium and magnesium removal in base metal leach circuits - Lorenzen, L.; Eksteen, Jacques; Pelser, M.; Aldrich, Chris; Georgalli, G. (Southern African Institute of Mining and Metallurgy, 2009)
An effective electrowinning process in hydrometallurgical industry requires fluoride levels in the base metal solution to be less than 10 mg/l. Selective removal of the fluoride ions from base solution isthus desired, if fluoride was added to control calcium and magnesium in the circuit. Consequently, adsorption of fluoride onto activated alumina was studied in a batch and a column set-up. Theeffects of base metal solution pH, temperature, initial concentration and flow rate on activated alumina performance were investigated in either a batch or column configuration. A two-level factorialexperimental design was implemented in studying column dynamics. Results demonstrate that activated alumina is an effective adsorbent for selective removal of fluoride from base solution. In the batch operation, fluoride was removed to values below the maximum allowable concentration (10 mg/l) when pH was = 8. In the column adsorption step at 55°C and 600mg/l initial concentration, up to 16 bed volumes were processed before breakthrough level was reached. Desorption step using 1% sodiumhydroxide solution achieved an elution of 8 bed volumes. The activated alumina (AA) had a capacity of 8.65 gF/l AA at the 10 mgF/l fluoride breakthrough level during the column adsorption test.